M2 polarization of tumor‐associated macrophages is dependent on integrin β3 via peroxisome proliferator‐activated receptor‐γ up‐regulation in breast cancer. Issue 4 (29th April 2020) - Shu, Yuxin; Qin, Menghao; Song, Yue; Tang, Qing; Huang, Yahong; Shen, Pingping; Lu, Yan
Summary: Macrophages are particularly abundant and play an important role throughout the tumor progression process, namely, tumor‐associated macrophages (TAM) in the tumor microenvironment. TAM can be polarized to disparate functional phenotypes, the M1 and M2 macrophages. M1‐like type macrophages are defined as pro‐inflammatory cells involved in killing cancer cells, while M2‐like type cells can specially promote tumor growth and metastasis, tissue remodeling and immunosuppression. In this study, we first found that integrin β 3 was highly expressed on the surface of TAM, both in vivo and in vitro, that displayed the M2‐like characteristics. Under intervention of CYC or triptolide, the integrin β 3 inhibitors, the M2 polarization of TAM could be inhibited. Moreover, in the cell model of M2 polarization, either blockade or knockout/knockdown of integrin β 3 could also suppress macrophage M2 polarization, which suggested that the M2 polarization was dependent on integrin β 3. Using knockdown of peroxisome proliferator‐activated receptor‐ γ (PPAR γ ), an M2 regulator, we found that expression and activation of PPAR γ participated in M2 polarization that was mediated by integrin β 3. Finally, to verify the activity of integrin β 3 inhibitors on TAM in vivo, 4T1 tumor‐bearing mice were treated with CYC or triptolide; in response, the M1/M2 ratio of TAM was up‐regulated, while the infiltration of total lymphocytes into tumor tissue was not altered. In general, our study found a connection between integrin β 3 and macrophage polarization, which provides a strategy for facilitating M2 to M1 repolarization and reconstructing the tumor immune microenvironment. Abstract : Integrin β 3 was highly expressed on the surface of TAM, both in vivo and in vitro, that displayed M2‐like characteristics. Either blockade or knockout/knockdown of integrin β 3 could suppress macrophage M2 polarization in vivo and in vitro, which suggested that the M2 polarization was dependent on integrin β 3. Integrin β 3 blockade suppresses M2 polarization mediated by PPAR γ .